2022
DOI: 10.3389/fpsyg.2022.880646
|View full text |Cite
|
Sign up to set email alerts
|

Getting Through the Crisis Together: Do Friendships Contribute to University Students’ Resilience During the COVID-19 Pandemic?

Abstract: Social contacts and social support represent resources that contribute to resilience. However, the COVID-19 pandemic and the associated measures, including contact restrictions, posed challenges for young adults’ social networks, in particular for their friendships. Employing a mixed-method approach, we investigated the pandemic’s effects on friendships and their role in successfully navigating the crisis. We combined a qualitative approach based on narratives and in-depth interviews and a quantitative approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…These findings align with similar results obtained by Haider et al ( 49 ) where Austrian students expressed a desire to talk to someone without specialized expertise, including friends and family. Social contacts and support play a pivotal role during times of stress, serving as essential resources contributing to resilience ( 73 ). A qualitative online survey conducted by Schaffler et al ( 38 ) in December 2020 revealed that, especially in the initial year of the COVID-19 pandemic, social contacts were the primary source of support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings align with similar results obtained by Haider et al ( 49 ) where Austrian students expressed a desire to talk to someone without specialized expertise, including friends and family. Social contacts and support play a pivotal role during times of stress, serving as essential resources contributing to resilience ( 73 ). A qualitative online survey conducted by Schaffler et al ( 38 ) in December 2020 revealed that, especially in the initial year of the COVID-19 pandemic, social contacts were the primary source of support.…”
Section: Discussionmentioning
confidence: 99%
“…While the present dataset also emphasized the importance of social contacts as a main source of support ( 48 ), it is noteworthy that the percentage of individuals relying on social contacts declined from 46% in 2020/21 to 36.2% in 2022. Changes and challenges in friendships were evaluated by Kulcar et al ( 73 ) highlighting the difficulty of forming new acquaintances during the COVID-19 pandemic and a decrease in the number of relationships as the pandemic persisted. Consequently, building and maintaining friendships were negatively affected during this period ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large portion of the existing research examines social anxiety among university students. Many university students had high levels of social anxiety prior to the COVID-19 pandemic, hereafter referred to as "the pandemic" 10,11,12,13,14 . Archbell and Coplan 15 examined the link between social anxiety in university students, academic communication and student experiences prior to the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Among the results, social anxiety was negatively correlated to communication with professors, student experiences and socio-emotional functioning 14 . Research during the pandemic found that young adults were especially vulnerable to the mental health impacts of the pandemic 11,13,14,16 . The prolonged period of lockdown and social isolation increased the rates of social anxiety among university students 7,16 .…”
Section: Introductionmentioning
confidence: 99%